New Genes for Resistance to Whitebacked Planthopper in Rice - Angeles, Enrique R.; Khush, G.S.; Heinrichs, E.A. (Wiley, 1981)
The inheritance of resistance to whitebacked planthopper, Sogatella furcifera (Horvath), in 12 resistant rice Oryza sativa L. cultivars was studied. This study was undertaken to identify additional genes for resistance and to determine the allelic relationships of newly identified genes and Wbph. The bulk seedling test was utilized for testing the hybrid materials for resistance to the insect. The reactions of F1, F2, and F3 populations from the crosses of resistant cultivars with ‘TN1’ revealed that resistance in ‘P580,’ ‘Sathra 267,’ ‘Sonpattar 45,’ ‘Sufaida 172,’ ‘ARC 10239,’ ‘Jhinuwa,’ ‘N32,’ and ‘Latighawar’ is controlled by a single dominant gene. Resistance of ‘IR2035‐117‐3’ is governed by two independent dominant genes. Similarly, resistance of ‘Colombo,’ ‘368,’ and ‘WC 1240’ is conferred by one dominant and one recessive gene that segregate independently of each other.P580, Sathra 267, Sonpattar 45, Sufaida 172, Jhinuwa, N32, and Latighawar have the Wbph gene for resistance. This gene was redesignated as Wbph 1. ARC 10239 has a single dominant gene which segregates independently of Wbph 1. It is designated as Wbph 2. IR2035‐117‐3 is homozygous for Wbph 1 and Wbph 2 whereas Colombo has Wbph 2 and another recessive gene. Wbph 1 and a recessive gene confer resistance in WC 1240 and 368.